1997
DOI: 10.1136/gut.41.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphism of the pepsinogen C gene and gastric body ulcer: the genetic predisposition is not associated with Helicobacter pylori infection

Abstract: Background and aims-The genetic trait plays a part in the pathogenesis of peptic ulcer disease. To identify a DNA marker for peptic ulcer disease, the association between the restriction fragment length polymorphism (RFLP) of the pepsinogen C (PGC) gene and peptic ulcer disease was investigated. Patients and methods-One hundred and seventy seven unrelated controls, 75 patients with gastric ulcer, and 70 with duodenal ulcer were studied. PGC-RFLP was analysed by polymerase chain reaction (PCR), and the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…The results of a Chinese study (57.1-61.0 %) and a Portuguese study (72.4 %) were similar to our observation [7]. However, another Asian study (Japanese: 46.3 %) showed discordance with our findings [6,36]. We also found that carriage of allele 1 (310 bp, the shorter allele) was infrequent among patients with GC compared to HC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of a Chinese study (57.1-61.0 %) and a Portuguese study (72.4 %) were similar to our observation [7]. However, another Asian study (Japanese: 46.3 %) showed discordance with our findings [6,36]. We also found that carriage of allele 1 (310 bp, the shorter allele) was infrequent among patients with GC compared to HC.…”
Section: Discussionsupporting
confidence: 82%
“…We observed that allele 1 carriage was infrequent among patients with GC who were seropositive for H. pylori. However, a previous Japanese casecontrol study showed no differences in allelic frequency of PG-II polymorphisms among patients with gastric body ulcer in the presence and absence of H. pylori infection [36]. H. pylori colonizes in the stomach mucosa and increases the risk of GC, being closely related to the level of serum PGs.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, it should be noted that 20 out of 21 studies demonstrated the reduced level of serum gastrin by H. pylori eradication therapy, suggesting improvement of inflammation in the corpus (table 2) [18, 19, 21, 22,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49]. The level of somatostatin and the number of D cells have been reported to increase after therapy [38, 45,][50], although this requires biopsy specimens for the estimation.…”
Section: Pepsinogen Gastrin and Gastric Acid Secretionmentioning
confidence: 99%
“…50 Some research results suggest that there is a significant association between genetic polymorphism at the PGR-RFLP gene locus and gastric body ulcer. 51 Genetic play an important role in ulcer pathogenesis. The concordance for peptic ulcer in identical twins is approximately 50%, and the lifetime prevalence of developing ulcer in first degree relatives of ulcer patients is about three-fold greater than in the general population.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%